EVALUASI IMPLEMENTASI PROGRAM PEMBANGUNAN DAN PEMBERDAYAAN MASYARAKAT DESA (P3MD) DALAM MEWUJUDKAN DESA MANDIRI DI DESA KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR - Basir S.Sos; Muammar Alkadafi; Mustiqowati Ummul Fithriyyah (Jurnal EL-RIYASAH, 2020)
The Village Community Development and Empowerment Program (P3MD) is a strategic government program. The implementation of the program in Kualu Nenas Village has not had a significant impact on changing the status of the village, from a developing village to a developed and independent village. The research objective was to determine program implementation and to determine the impact of the program in Kualu Nenas Village. The research method used a qualitative approach, with evaluative research type. Sources of data obtained through observations at the target location of program activities, in-depth interviews, with key informants; Village Head, Village Officials, BPD, LKMD, community leaders and community group representatives, village assistants. Data was also obtained through distributing questionnaires to 30 informants who were selected by purposive sampling. Research result. The implementation of the Program covers 4 (four) areas of activity, namely activities of village administration, village development, village community empowerment, village communities. The implementation of activities has not been fully carried out properly, not all program activities are carried out in accordance with the activity items, according to the program implementation instructions and the specific objectives of the program. There has been no innovation (change) that has led to the achievement of a change in the status of the village from being left behind to becoming a developed and independent village. The programs that have been implemented have not been fully felt by the community, especially in the aspect of developing community productive economic facilities in the agricultural and plantation sectors, and increasing community capacity.